Aural rehabilitation of people with disabilities - Oyiborhoro, John M. A. (Amsterdam ; Boston : Elsevier Academic Press, 2005)
This book provides a comprehensive audiological assessment and management of people with disabilities.
Preliminaries; CONTENTS; CONTRIBUTORS; FOREWORD; ACKNOWLEDGMENTS; CHAPTER1 Overview of Disabilities; CHAPTER 2 Cerebral Palsy/Developmental Disabilities; CHAPTER 3 HIV/AIDS; CHAPTER 4 People with Visual Impairment; CHAPTER 5 Older Adults with Dementia or Alzheimer's Disease; CHAPTER 6 Otitis Media: Diagnosis and Management; CHAPTER 7 Cerumen Management; CHAPTER 8 Amplification and Assistive Technology; CHAPTER 9 Augmentative and Alternative Communication; CHAPTER10 RESPECTFUL Counseling: A Blueprint for Practice; SUBJECT INDEX; AUTHOR INDEX
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Hard of hearing people -- Rehabilitation; People with disabilities -- Rehabilitation; Audiology; Correction of Hearing Impairment; Persons with Disabilities -- rehabilitation; Audiology; Audiologie; HEALTH & FITNESS -- Hearing & Speech; MEDICAL -- Audiology & Speech Pathology; People with disabilities -- Rehabilitation; Audiology; Rehabilitation of Hearing Impaired; Disabled Persons -- rehabilitation; Hearing impaired -- Rehabilitation; Audiology; Hearing impaired -- Rehabilitation; People with disabilities -- Rehabilitation; Percepção auditiva (reabilitação)